Prevalence of advanced hepatic fibrosis and individualization of associated risk factors by Bayesian analysis in MASLD patients in French cardio-metabolic health networks - Michel Doffoel; Frédéric Chaffraix; Archia Chahard; Dominique Gras; Odile Bonomi; Corinne Bildstein; Simona Tripon; Maude Royant; Nicolas Meyer (PLoS ONE, 2025)
The aim of this study was to determine the prevalence of advanced hepatic fibrosis and to individualize using Bayesian analysis its associated risk factors in patients with metabolic dysfunction-associated steatotic liver disease (MASLD) being cared for in three Alsatian cardio-metabolic health networks in the North East of France. Overall, 712 patients aged ≥18 years with a female predominance were included into a prospective, cross-sectional, and observational study. Advanced fibrosis and severe steatosis were evaluated using transient elastography (FibroScan®). The proportion of MASLD patients was 80% and 84% in women and men (difference -4.2% [-10.0; 1.9]), respectively. Advanced fibrosis was observed in 11% of patients, being more common in men (16.9%) than women (7.5%) (difference 9.4 [4.3–15.0]). Severe steatosis was also more common in men (74.9%) than women (63.4%) (difference 11.4 [4.2–18.2]). Only three of the tested variables were likely associated with advanced fibrosis: gender (OR: 1.78 [1.17–2.68]; Pr [OR >1] = 1), T2DM (OR: 1.54 [1–2.37]; Pr [OR >1] = 0.97) and hypertriglyceridemia (OR: 1.49 [0.97–2.27]; Pr (OR >1) = 0.97). In conclusion, this study confirmed the usefulness of assessing hepatic fibrosis in patients with metabolic dysfunction. Therefore, access to FibroScan® should be facilitated in all cardio-metabolic health networks.